Allergic Fungal Rhinosinusitis in Chronic Rhinosinusitis - Shrestha, S; Kafle, P; Akhter, J; Acharya, L; Khatri, R; KC, T (Journal of Nepal Health Research Council, 2011)
Background: Rhinosinusitis is the inflammation of nasal and paranasal sinus mucosa and is associated with mucosal alteration ranging from inflammatory thickening or gross nasal polyp formation.The main objective of this study is to etermine the prevalence of allergic fungal rhino sinusitis among the patients having chronic rhino sinusitis with or without polyps who under goes functional endoscopic sinus surgery.Methods: The patient with chronic rhinosinusitis with or without polyp who FESS were studied. Surgical specimens were sent for mycology and histopathological analysis for identification of fungus.Results: Headache 41(82%) and nasal block 45(90%) were the commonest clinical presentation. Out of 50 patients,fungal elements were detected by KOH in 8(16%) of cases and histopathological examination in 11(22%) of cases.Conclusions: Allergic Fungal Rhinosinusitisis a common disorder in patients with chronic rhinosinusitis, it needdifferent specific tests for the diagnosis, a more specific diagnostic tests are fungus culture, and IgE to fungal antigen and skin test are needed for definite diagnosis.Keywords: allergy, fungus, rhinosinusitis, sinusitis